Scaling of damage mechanism for additively manufactured alloys at very high cycle fatigue - B. S. Voloskov; M. V. Bannikov; Y. V. Bayandin; O. B. Naimark; I. V. Sergeichev (Scientific Reports, 2024)
Abstract A comparative analysis of fracture mechanisms in high- and very high- cycle fatigue (HCF, VHCF) regimes was carried out based on the results of multifractal analysis of the fracture surfaces of additively manufactured 316L stainless steel samples. In terms of scale invariants, the morphology of fracture surfaces in HCF and VHCF regimes inside and outside the fine granular area is shown. The analysis demonstrated that chaotic patterns of relief formation prevail in the crack initiation zone of VHCF samples. However, there is a self-similar relief with a pronounced correlation in the crack propagation area. The relief of the crack growth areas for HCF and VHCF samples are similar to each other.